Impacts of nudging in forest management - Pokharel, Padamraj (2021)
Intense forest exploitation has decreased ecological services and has led to the loss of biodiversity. In Finland, a shift towards Continuous Cover Forestry (CCF) from Rotation Forest Management (RFM) could provide more ecosystem services and conserve the forest's biodiversity. To encourage such a shift, there is the need to find tools that leverage change in management practices in favor of CCF. Nudge is a behavioral change tool that can change people’s decision-making unconsciously. Here, I explored the impact of nudging on forest owners and professional’s intention to either practice or recommend CCF. I did so by using online experiment survey data from a previous study done by Isoaho et al. (2019), where stakeholders had to report the intention of using/recommending CCF after reading one of four texts comparing the two main management regimes. The text had a range of bias from favoring RFM to favoring CCF. I also evaluated how the respondent characteristics (i.e., distance to and area of owned forest, age, gender, education, and specific knowledge about forest management, economics, and the environment) may impact the nudging effect. Professionals were not affected by the nudge text, whereas the forest owner’s intention to use CCF was conditional on the text version they read. To promote increased adoption of CCF, forest owners should be provided with text that includes no or a nudging slightly favoring CCF. Distance from residence to owned forest property and, to some extent, owned forest area were related to the effect of the nudge. I conclude that a better understanding of nudges can help to better frame managements options for forest sustainability. However, a clear challenge is that professionals, that are not positive about increasing CCF and are often consulted by private owners, did not react to nudge.